In vitro mechanical behavior and in vivo healing response of a novel thin-strut ultrahigh molecular weight poly-l-lactic acid sirolimus-eluting bioresorbable coronary scaffold in normal swine. (1st July 2019) - Cheng, Yanping; Gasior, Pawel; Ramzipoor, Kamal; Lee, Chang; McGregor, Jenn C.; Conditt, Gerard B.; McAndrew, Thomas; Kaluza, Grzegorz L.; Granada, Juan F.
Abstract: Background: New generation bioresorbable scaffolds (BRS) promise to improve the outcomes of current generation BRS technologies by decreasing wall thickness while maintaining structural strength. This study aimed to compare the biomechanical behavior and vascular healing profile of a novel thin-walled (98 μm) sirolimus-eluting ultrahigh molecular weight BRS (Magnitude, Amaranth Medical) to the Absorb everolimus-eluting bioresorbable vascular scaffold (Abbott Vascular). Methods and results: In vitro biomechanical testing showed lower number of fractures on accelerated cycle testing over time (at 21K cycles = 20.0 [19.0–21.0] in Absorb versus 0.0 [0.0–1.0] in Magnitude-BRS). Either Magnitude (n = 43) or Absorb (n = 22) was implanted in 65 coronary segments of 22 swine. Scaffold strut's coverage was evaluated using serial optical coherence tomography (OCT) analysis. At 14 days, Magnitude-BRS demonstrated a higher percentage of embedded struts (97.7% [95.3, 100.0] compared to Absorb (57.2% [48.0, 76.0], p  = 0.003) and lower percentage of uncovered struts (0.0% [0.0, 0.0] versus Absorb 5.5% [2.6, 7.7], p  = 0.02). Also, it showed a lower percent late recoil (−1.02% [−4.11, 3.21] versus 4.42% [−1.10, 8.74], p  = 0.04) at 28 days. Histopathology revealed comparable neointimal proliferation and vascular healing responses between two devices up to 180 days. Conclusion: A new generation thin walled (98-μm) Magnitude-BRS displayed a promising biomechanical behavior and strut healing profile compared to Absorb at the experimental level. This new generation BRS platform has the potential to improve the clinical outcomes shown by the current generation BRS. Highlights: Thick-strut BRS is associated with increased risk of clinical adverse events. A novel thinner-strut BRS displayed superior biomechanical and strut healing performance. Potential to improve the clinical performance of BRS by displaying DES-like properties